Development of Point-of-Care Biosensors for COVID-19 - Choi, Jane Ru (Frontiers in Chemistry, 2020)
Coronavirus disease 2019 (COVID-19) outbreak has become a global pandemic. The deleterious effects of coronavirus have prompted the development of diagnostic tools to manage its spread. While conventional technologies such as quantitative real time polymerase chain reaction (qPCR) have been broadly used to detect COVID-19, they are time-consuming, labor-intensive and are unavailable in remote settings. Point-of-care (POC) biosensors, including chip-based and paper-based biosensors are typically low-cost and user-friendly, which offer a tremendous potential for rapid medical diagnosis. This mini review article discusses the recent advances in POC biosensors for COVID-19. First, the development of POC biosensors which are made of polydimethylsiloxane (PDMS), papers and other flexible materials such as textile, film and carbon nanosheets are reviewed. The advantages of each biosensors along with the commercially available COVID-19 biosensors are highlighted. Lastly, the existing challenges and future perspectives of developing robust POC biosensors to rapidly identify and manage the spread of COVID-19 are briefly discussed.